Study of ship resistance prediction method for laterally drifting ship [electronic resource] - Muhammad Shafie Che Mangsor, 1985-; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009